Aortic Dissection Type a in Combination with Acute Anterior Myocardial Infarction. Myocardial Protection - Georgi Stoitsev; Veselin Gavrilov; Vassil Gegouskov (Journal of Biomedical & Clinical Research)
Acute aortic dissection is an extremely serious condition with a high mortality risk. Symptoms may mimic other emergencies such as myocardial ischemia, often leading to misdiagnosis. A combination between coronary hypoperfusion and aortic dissection is relatively rare, but when present it could be fatal. Early diagnosis and correct surgical approach are essential to success in those patients and the high mortality rate requires improvement of myocardial protection. Development of acute cardiac ischemia on top of mandatory global ischemia is a serious precondition for a severe postcardiotomy syndrome, and only excellent cardiac protection can lead to successful surgical intervention.